Finite-temperature dynamics of the Anderson model - Logan, D; Dickens, N (2002)
The recently introduced local moment approach (LMA) is extended to encompass single-particle dynamics and transport properties of the Anderson impurity model at finite temperature, T. While it is applicable to arbitrary interaction strengths, primary emphasis is given to the strongly correlated Kondo regime (characterized by the T = 0 Kondo scale ωK). In particular the resultant universal scaling behaviour of the single-particle spectrum D(ω T) ≡ F(ω/ωK; T/ωK) within the LMA is obtained in closed form; leading to an analytical description of the thermal destruction of the Kondo resonance on all energy scales. Transport properties follow directly from a knowledge of D(ω; T). The (T/ωK)-dependence of the resulting resistivity ρ(T), which is found to agree rather well with numerical renormalization group calculations, is shown to be asymptotically exact at high temperatures; to concur well with the Hamann approximation for the s-d model down to T/ωK ∼ 1, and to cross over smoothly to the Fermi liquid form ρ(T) - ρ(0) ∝ - (T/ωK)2 in the low-temperature limit. The underlying approach, while naturally approximate, is moreover applicable to a broad range of quantum impurity and related models.